Alat Bantu Training Elektronika Berbasis Internet Of Things dengan Logika Fuzzy Menggunakan NODEMCU - Lukman Medriavin Silalahi; Agus Dendi Rochendi; Irfan Kampono; Muhamad Husni; Raden Sutiadi (Sekolah Tinggi Teknik - PLN, 2021)
Electronic training activities are still carried out conventionally, namely through a face-to-face system. The trainer has to check the trainees' measurement scores manually, this takes a long time. In addition, during the Covid-19 pandemic, human interaction is limited. Therefore it is necessary to make a tool that can help the training process. The proposed IoT-based electronic training tool uses nodeMCU, with a MySQL database system using IoT (Internet of Things) technology. Data communication media uses Wifi (IEEE 802.11n) with nodeMCU 8266 and INA219 sensors. The data is directly displayed through the internet browser media(PHP). From the results of our research, this tool can monitor the implementation of training for a distance of 8 meters and the sensor response time is less than 1 second. The sensor sensitivity level reaches 99.01% with a measurement accuracy of 0.01. With this tool, checking measurement results can be done quickly and can be done from anywhere.